Benchmarking β‐Ga2O3 Schottky Diodes by Nanoscale Ballistic Electron Emission Microscopy. (22nd January 2020) - Buzio, Renato; Gerbi, Andrea; He, Qiming; Qin, Yuan; Mu, Wenxiang; Jia, Zhitai; Tao, Xutang; Xu, Guangwei; Long, Shibing
Abstract: Monoclinic beta‐phase gallium oxide (β‐Ga2 O3 ) is an ultrawide‐bandgap semiconductor, intensively studied as a viable candidate for next‐generation power electronics, optoelectronics, and extreme environment electronics. Schottky contacts to β‐Ga2 O3 are of paramount importance to this end; however, they are not yet fundamentally understood. Intrinsic sources of interfacial disorder, including oxygen‐related defects and extrinsic fabrication factors, are thought to greatly determine the properties of such contacts, for example by originating Fermi level pinning and causing patches with different Schottky barrier heights (SBHs). Ballistic electron emission microscopy (BEEM) is used to probe band bending and interfacial inhomogeneity at the nanoscale for prototypical Au/ and Pt/(100)β‐Ga2 O3 single crystal Schottky barrier diodes. It is shown that SBH fluctuations amount to 40–60 meV under vacuum, occurring over length scales of tens of nanometers. Furthermore, a remarkable SBH modulation of ≈0.2 eV takes place upon exposure of devices from vacuum to ambient air. Such findings—better obtained by BEEM than by macroscale approaches—point to the existence of an ubiquitous inhomogeneous interfacial layer, controlling band bending and ambient sensitivity via oxygen ionosorption and interface redox chemistry. This study ascribes a key role to interfacial oxygen vacancies, and has practical implications for transport modelling and interface engineering. Abstract : The increasing interest in the ultrawide‐bandgap oxide semiconductor β‐Ga2 O3 demands deep understanding of its Schottky contacts. Ballistic electron emission microscopy is used to directly probe nanoscale band bending and interfacial inhomogeneity for prototypical (100) single‐crystal rectifiers. Results tightly relate the Schottky barrier height to interfacial oxygen vacancies, and give a basis reference to advance transport modelling and interface engineering.